PSYCHOLOGICAL TRAUMATIC POST-PLACENTA RETENSION WITH THE DESIRE TO GET PREGNANT - Shanty Natalia; Niah Susianti; Miftakur Rohmah (Universitas STRADA Indonesia, 2024)
Negative birth experiences can even lead to severe psychological trauma in women. Post-copy trauma can affect mother-child relationships, against husbands, even the way they treat their children. Based on data in 2023 from January to July at Pratama Sebuku Hospital, 36 mothers were given birth data, and five mothers had placenta retention cases with psychological trauma. This research uses a qualitative research design with a Case Study Research approach. With the accidental sampling technique, samples of 5 informants were obtained. using the method of interviewing five subjects of postpartum mothers with a history of placenta retention. These subjects were investigated in response to post-placental psychological trauma with the desire to become pregnant again.